Neutron-neutron correlation in the halo dissociation of light exotic nuclei - Yamashita, M. T. [UNESP]; Frederico, T.; Tomio, Lauro [UNESP] (American Physical Society (APS), 2005)
We present model results for the two-halo-neutron correlation functions, Cnn, for the dissociation process of light exotic nuclei modelled as two neutrons and a core. A minimum is predicted for Cnn as a function of the relative momentum of the two neutrons, pnn, due to the coherence of the neutrons in the halo and final state interaction. Studying the systems Be14, Li11, and He6 within this model, we show that the numerical asymptotic limit, Cnn 1, occurs only for pnn3400MeV/c, while such limit is reached for much lower values of pnn in an independent particle model as the one used in the analysis of recent experimental data. Our model is consistent with data once the experimental correlation function is appropriately normalized. © 2005 The American Physical Society.